The Inevitable Challenge of Ethical Dilemmas in Optometry, Part 2: Professional Relationships and Practices in the Spotlight - Faucher, Caroline; Verni, Ariana; Rezk, Marina (Canadian Journal of Optometry, 2022)
Health care professionals sometimes have to choose between options that are each less than optimal, and thereby risk compromising an ethical principle. Despite the impact they can have on these professionals and the population they serve, ethical dilemmas have never been studied in optometry. Objective. This article is the second in a series of three reporting the results of a study that aimed to identify and describe the ethical dilemmas faced by optometrists. Method. A total of 240 optometrists completed an online questionnaire concerning ethical dilemmas encountered during their career. Results. A major source of ethical dilemmas for optometrists is conflicts with other optometrists, as well as with opticians and ophthalmologists. Other situations, such as being confronted with cases at the limit of one’s competency and the disclosure of personal information, are also important ethical issues. Conclusion. Optometrists experience ethical questioning that is likely to cause them stress and compromise the well-being of the public. The next and final article in this series will reveal ethical dilemmas concerning the optometrist/patient relationship and offer suggestions for optometrists to be better prepared for dealing with the various ethical issues related to the practice of their profession.